The Effect of Spiritually Integrated Chemistry Learning on Learning Outcomes Moderated by Spiritual Quotient (SQ) Levels - Andini Zahra; Ayi Darmana; Denada Septiani Yesa (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Indonesian students' science performance remains low based on PISA 2022 results, particularly in abstract chemistry concepts such as acid-base. This study aims to analyze the effect of chemistry learning integrated with spiritual values on students' learning outcomes moderated by Spiritual Quotient (SQ) levels. A quasi-experimental method with a 2 × 2 factorial design was employed, involving 60 eleventh-grade students selected through purposive sampling. The experimental class (n = 30) applied Problem Based Learning (PBL) integrated with seven spiritual values (awareness, elegance, meaningfulness, transcendence, truth, peace, wisdom) through motivation, reflection, and contemplation, while the control class (n = 30) used PBL without spiritual values integration. Data were collected using a 20-item multiple-choice test (KR-20 = 0.95) and a 19-item SQ questionnaire adapted from Indaty N. (2022) based on Zohar and Marshall's (2000) theory (Cronbach's alpha = 0.872). Two-Way ANOVA results revealed that spiritually integrated chemistry learning significantly improved learning outcomes (F = 25.697, p = 0.000). SQ level also significantly influenced learning outcomes (F = 46.060, p = 0.001). However, no significant interaction was found between learning model and SQ level (p = 0.224), indicating that both variables independently affect learning outcomes. Low SQ students in the experimental class (M = 81.79) achieved scores comparable to high SQ students in the control class (M = 85.00), suggesting that spiritual values integration can compensate for lower SQ levels. State of novelty in this study concludes that integrating spiritual values into chemistry learning enhances academic achievement and supports holistic education by connecting scientific concepts with students' life values.